Small Resistance Artery Disease and ACE2 in Hypertension: A New Paradigm in the Context of COVID-19 - Galán, María; Jiménez-Altayó, Francesc (Frontiers in Cardiovascular Medicine, 2020)
Cardiovascular disease causes almost one third of deaths worldwide, and more than half are related to primary arterial hypertension (PAH). The occurrence of several deleterious events, such as hyperactivation of the renin–angiotensin system (RAS), and oxidative and inflammatory stress, contributes to the development of small vessel disease in PAH. Small resistance arteries are found at various points through the arterial tree, act as the major site of vascular resistance, and actively regulate local tissue perfusion. Experimental and clinical studies demonstrate that alterations in small resistance artery properties are important features of PAH pathophysiology. Diseased small vessels in PAH show decreased lumens, thicker walls, endothelial dysfunction, and oxidative stress and inflammation. These events may lead to altered blood flow supply to tissues and organs, and can increase the risk of thrombosis. Notably, PAH is prevalent among patients diagnosed with COVID-19, in whom evidence of small vessel disease leading to cardiovascular pathology is reported. The SARS-Cov2 virus, responsible for COVID-19, achieves cell entry through an S (spike) high-affinity protein binding to the catalytic domain of the angiotensin-converting enzyme 2 (ACE2), a negative regulator of the RAS pathway. Therefore, it is crucial to examine the relationship between small resistance artery disease, ACE2, and PAH, to understand COVID-19 morbidity and mortality. The scope of the present review is to briefly summarize available knowledge on the role of small resistance artery disease and ACE2 in PAH, and critically discuss their clinical relevance in the context of cardiovascular pathology associated to COVID-19.